ANALISIS FUNDAMENTAL SAHAM TERHADAP PERTUMBUHAN PERUSAHAAN (STUDI KASUS PADA PT. BLUE BIRD, TBK.) - Sunaryono Sunaryono (Jurnal Ekonomi STIEP, 2018)
The method of analysis using the fundamental strength of a country is called by fundamental analysis. In general, the fundamental strength of a country is shown by the country’s economic data. Fundamental analysis states that every stock has an intrinsic value. This analysis attempts to calculate the intrinsic value of a stock by using the fundamental data of the “ Company’s Financial Statements “, such as capital structure,earning devidends, sales, expenditure etc. This analysis will compare the intrinsic value with the market value to determine whether the market price of shares has reflected its intrinsic value or has not. The purpose of this study is to find out the company’s fundamental analysis with the liquidity ratio, the company’s growth, and the impact of the analysis on the company’s growth. The result of the research indicates that the two public companies analyzed for five years in terms of cash and cash equivalents, inventories, current assets and current liabilities is that PT. Blue Bird, Tbk was stable. Concerning profit growth, PT. Blue Bird, Tbk yielded profit. The analysis of those factors shows that it has positive effect for PT. Blue Bird, Tbk which causes many investors will invest their funds. Keywords : ; ; company’s growth